Necrotizing Enterocolitis Is Not Associated With Sequence Variants in Antioxidant Response Genes in Premature Infants. Issue 3 (March 2016) - Sampath, Venkatesh; Helbling, Daniel; Menden, Heather; Dimmock, David; Mulrooney, Neil P.; Murray, Jeffrey C.; Dagle, John M.; Garland, Jeffery S.
Abstract : ABSTRACT: Reactive oxygen species mediate intestinal injury in necrotizing enterocolitis (NEC), and yet the contribution of antioxidant response ( ARE ) gene polymorphisms to NEC risk remains unknown. Premature infants recruited in a multicenter study were genotyped for 6 ARE variants. Among 637 infants, 52 had NEC, and 22 developed surgical NEC. Gestational age <28 weeks ( P < 0.02) and African American race ( P = 0.03) were associated with NEC. The NFE2L2 (rs6721961), SOD2 (rs4880), GSTP1 (rs1695), NQO1 (rs1800566), GCLC (rs17883901), and HMOX1 (rs2071747) variants were not associated with medical or surgical NEC. This study does not support a role for common deleterious ARE variants in NEC. Abstract : Supplemental Digital Content is available in the text